2020
DOI: 10.3844/jcssp.2020.1220.1228
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Gradient ‎Method: A Developed Version to Resolve Unconstrained Optimization Problems

Abstract: One of the important methods that are widely utilized to resolve unconstrained optimization problems is the Conjugate Gradient (CG) method. This paper aims to propose a new version of the CG method on the basis of Weak Wolfe-Powell (WWP) line search. The assumption is bounded below optimization problems with the Lipschitz continuous gradient. The new parameter obtains global convergence properties when the WWP line search is used. The descent condition is established without using any line search. The performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…where 3) with the CG method in equation (28), where the step size satisfies (4) and (5). en, we obtain the results by using Lemmas 2 and 3, as well as Lemmas 4.1 and 4.2 in [10], where liminf k⟶∞ ‖g k ‖ � 0.…”
Section: Global Convergence Of Figure 1 With General Nonlinearmentioning
confidence: 66%
See 3 more Smart Citations
“…where 3) with the CG method in equation (28), where the step size satisfies (4) and (5). en, we obtain the results by using Lemmas 2 and 3, as well as Lemmas 4.1 and 4.2 in [10], where liminf k⟶∞ ‖g k ‖ � 0.…”
Section: Global Convergence Of Figure 1 With General Nonlinearmentioning
confidence: 66%
“…Meanwhile, for (y k− 1 + s k− 1 ), the direction y k− 1 is an essential term in obtaining the descent condition when multiplied by negative gradient. It is also useful in terms of efficiency, i.e., if this term goes to zero, the search direction will restart using the steepest descent method, avoiding equation (28) to cycle without reaching the solution.…”
Section: The New Search Directionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yousif et al [27] introduced a criterion that ensures the establishment of the descent search direction property and the global convergence of CG techniques under SW line search. Many researchers (see e.g., Refs [28][29][30][31][32]) have demonstrated that several numerical techniques for unconstrained optimization converge under the SW condition.…”
Section: Introductionmentioning
confidence: 99%